Quantifying the intersection of disability and homelessness in Massachusetts public schools in 2018–2019. (26th January 2022) - Rubenstein, Eric; Bock, Emily; Brochu, Paige; Byrne, Thomas
Abstract: Background: Homelessness has a major impact on the educational and health trajectories of children. Youth with disabilities may be especially vulnerable to experiencing homelessness, but little epidemiological work has been done to characterize dual disparity. Our goal was to describe the relationship between homelessness and disability among students (age 3–21) receiving public education in Massachusetts in 2018–2019. We evaluated the proportion of students with and without disabilities experiencing homelessness by county and school district. Methods: We used publicly available data from the United States and Massachusetts Department's of Education. These data used the McKinney Vento Homelessness Assistance Act definition of homelessness which is a lack of fixed, adequate, and regular housing, and disability was determined by the presence of an individualized education program or individualized family service plan. We calculated percentages of students with and without disabilities experiencing homelessness at the state, county, and district level and calculated and mapped risk of homelessness comparing students and without disability. We also determined the occurrence of disability among those experiencing homelessness. Results: In Massachusetts public schools, 3.5% of students with disabilities experienced homelessness compared with 2.4% of students without disabilities (relative risk 1.50, 95% CI: 1.47, 1.53). A greater proportion of students with disabilities experienced homelessness compared with students without disabilities in all counties. In sum, 24.8% of students experiencing homelessness had a reported disability. Conclusions: In Massachusetts public schools, a greater proportion of students with disabilities experience homelessness compared with students without disabilities, and disability is common among students experiencing homelessness. We hypothesize potential mechanisms, such as the financial cost of disability, that may lead to this finding. Findings support the need for additional funding and interventions for school districts and communities to better serve vulnerable students with disabilities experiencing homelessness.